2020
DOI: 10.1007/s00431-020-03852-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute viral bronchiolitis as a cause of pediatric acute respiratory distress syndrome

Abstract: The Pediatric Acute Lung Injury Consensus Conference (PALICC) published pediatric-specific guidelines for the definition, management, and research in pediatric acute respiratory distress syndrome (PARDS). Acute viral bronchiolitis (AVB) remains one of the leading causes of admission to PICU. Respiratory syncytial virus (RSV) is the most common cause of AVB. We aimed to evaluate the incidence of PARDS in AVB and identify the risk of RSV as a trigger pathogen for PARDS. This study is a retrospective single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…26 In the study of Ghazaly et al, RSV was found to be the most common factor in ARDS patients younger than 1 year old. 27 In our study, contrary to other studies, the most common factors in the development of ARDS were found to be influenza A/B, HBoV, and hMPV. The risk of developing ARDS was lower in patients younger than 1 year old.…”
Section: Discussioncontrasting
confidence: 99%
“…26 In the study of Ghazaly et al, RSV was found to be the most common factor in ARDS patients younger than 1 year old. 27 In our study, contrary to other studies, the most common factors in the development of ARDS were found to be influenza A/B, HBoV, and hMPV. The risk of developing ARDS was lower in patients younger than 1 year old.…”
Section: Discussioncontrasting
confidence: 99%
“…Acute bronchiolitis and pneumonia are major respiratory failure causes in children and infants (1,2). Approximately 15-20% of affected children require respiratory support and intensive care due to a rapid emergence of respiratory distress (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there has yet to be an effective pharmacologic treatment for PARDS, and care is supportive. In addition, PARDS is a heterogeneous condition due in part to differences among children in the underlying pathobiology, age (which impacts changes in the lungs, chest wall, and immune system associated with development), comorbidities (1–21), and inciting trigger (22–85).…”
mentioning
confidence: 99%